Peningkatan Kapasitas Disabilitas ODGJ dan Netra Melalui Pelatihan dan Pendampingan Psikososial di Balai Rehabilitasi - Wahjudin, Lisdawati; Hastika, Nunung; Nurhayati, Ai (Jurnal Pengabdian Tri Bhakti, 2023)
This training is a community service program that started from our initial approach when we met with ODGJ and Netra at the Wyata Guna Sentra. This training is designed in a structured way to provide knowledge and skills for ODGJ and increase the ability of the net on how to get social support and process their emotions and how to become empowered. These skills are needed to reduce the high social and economic and physical psychological burden on the family. Thus the ODGJ gets attention and humane treatment so that they get their rights. In the implementation of activities there are several things that need to be improved and require support from various parties, namely policy makers for funding and collaboration with service providers at the primary level. The form of community service activities includes providing cooking skills training for ODGJ in Wyata Guna with a total of 14 people planned for four meetings, but did not rule out the situation and conditions on the ground. The second target is the blinds who will be given additional activities in the form of psychosocial assistance by a team of FISIP UNLA lecturers and students. This activity is divided into three stages, namely 1) the assessment stage; 2) training and mentoring; 3) monitoring and evaluation. The results of the activity are expected to be useful for skills for ODGJ and blind so that there is an increase in cognitive, affective and psychomotor abilities.